Pelatihan dan Pendampingan Pembuatan Media Audio Visual dalam Pelestarian Budaya dan Pengembangan Destinasi Wisata Kampung Bali Bekasi - Yudhistira Ardi Poetra; Fina Zahra; Nurul Fauziah; Sakha Putri Andhina; Suci Rahmadhania (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Kampung Bali Bekasi is a tourist destination with elements of authentic Balinese culture in the city of Bekasi. This cultural tourism destination, which is more or less three years old, has attracted the interest of the public and the media to come and cover them. The enthusiasm of the people who came to visit there was mostly to treat their curiosity and share the moments there on the social media they used. However, this is not followed by the management of Kampung Bali Bekasi, which actually has an Instagram account as a medium of communication. However, it cannot be categorized as optimal because it does not produce audio-visual content there too often. Therefore, this activity aims to conduct training and assistance in making audio-visual media in preserving local culture and developing cultural tourism destinations in Kampung Bali Bekasi. This community service is carried out using a descriptive qualitative approach and narrative analysis. This activity resulted in two activities that were well received by the people of Kampung Bali Bekasi. First, training in making audio-visual media generates community understanding and knowledge on how to make good audio-visual content with the theme Kampung Bali Bekasi. Then the assistance in making audio visual media generates an understanding regarding the choice of social media and good forms of content so that Kampung Bali Bekasi can develop their cultural tourism destinations through social media.